Evaluation of abundance of aerobic bacteria in the rhizosphere of transgenic and non-transgenic alfalfa lines - Faragová, N; Faragó, J; Drábeková, J (Folia microbiologica, 2005)
Fourteen genetically modified lines of alfalfa (Medicago sativa) containing the gene Ov from Japanese quail, coding for a methionine-rich protein ovalbumin, were evaluated for nodulation ability and concentration of aerobic bacteria in the rhizosphere. The transgenic lines were derived from a highly regenerable genotype Rg9/I-14-22, selected from cv. Lucia. On selective media, a higher concentration of ammonifying bacteria, bacterial spores, denitrifying and nitrifying bacteria were observed in the rhizosphere of transgenic clonesand, on the other hand, lower concentration of cellulolytic bacteria and Azotobacter spp. compared with the rhizosphere of non-transgenic clone SE/22-GT2. A statistically significant difference in the concentration of all the bacterial types was found between samples taken from two types of substrates (i.e. sterile vs. nonsterile). Higher bacterial concentration (measured as colony forming units per g soil dry mass) were observed for all tested groups of culturable bacteria in the non-sterile substrate. The presence of Azotobacter spp. was found only in the rhizosphere of plants grown in non-sterile soil in which the highest number of fertile soil particles (97 %) was observed in transgenic clones SE/22-9-1-12 and SE/22-11-1-1S.1. Concentration of bacteria involved in the N cycle in the soil was increased in the rhizosphere of transgenic clones and decreased in the rhizosphere of non-transgenic plants compared with the average value. In spite of some differences in colony numbers in samples isolated from the root rhizosphere of transgenic and nontransgenic alfalfa plants, we could not detect any statistically significant difference between individual lines.
Keywords: Quaternary Ammonium Compounds; Soil Microbiology; Bacteria, Aerobic; ovalbumin; Ovalbumin; Plants, Genetically Modified; kvartérní amoniové sloučeniny; Plant Roots; aerobní bakterie; kořeny rostlin; Cellulose; spory bakteriální; zvířata; geneticky modifikované rostliny; půdní mikrobiologie; celulosa; Azotobacter; Spores, Bacterial; Medicago sativa; Animals